ACTIVE APPLICATION OF LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES OF THEATER ASPECTS IN CLASS X ARTS AND CULTURE LEARNING MADRASAH ALIYAH ALLU - Ardi Sikai (Universitas Negeri Makassar, 2021)
Active Application of Learning to Improve Student Learning Outcomes to the Aspects of Theater in Learning Arts and Culture Class X Madrasah Aliyah Allu. Department of Performing Arts, Department of Educational Education, Faculty of Art and Design, Makassar State University. Advisor I Hamrin, S.Pd, M.Sn. And Advisor II Dr. Andi Ihsan, S.Sn, M.Pd.This researcher aims to increase students' interest in learning about art and culture aspects of theater class X MADRASAH ALIYAH ALLU through active learning methods, which are active learning methods which will then influence student learning outcomes in the art and culture learning process of class X MADRASAH ALIYAH ALLU, Bangkala District Jeneponto.In accordance with this type of research, namely Classroom Action Research, the researcher has three stages of activity in the form of cycles, namely Pre Cycle, Cycle I, Cycle IIBased on the results of the provision of the Preliminary Test (Pre-Cycle) the data obtained student learning outcomes have a percentage of classical completeness 20% with an average value of 54.3. In the first cycle student learning outcomes have a percentage of 43% with an average value of 61.33. In cycle II student learning outcomes have a classical percentage of completeness 80% with an average value of 77. The results of research conducted prove that increasing student learning outcomes, prove by, students follow learning through the application of active learning that can be done in the teaching process and teacher performance .Keywords: Active Learning, Student learning interest outcomes in learning